2022
DOI: 10.3389/fphys.2021.812290
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Cancer Status Among Middle-Aged and Older Chinese: A Population-Based, Cross-Sectional Study

Abstract: BackgroundThe relative contributions of demographic and lifestyle behaviors to the association between physical activity (PA) and cancer are poorly understood. This study assesses the relationship between PA level and cancer status considering the full activity spectrum within a large and representative Chinese population.MethodsData were derived from the Chinese Health and Retirement Longitudinal Study (using four-stage stratified probability-proportional-to-size sampling), including 416 cancer survivors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Since other studies reported a decrease in physical activity and fitness and an increase in weight gain during anticancer therapy ( 1 , 2 ), routine counselling appears to be insufficient to achieve a long-lasting effect on the patient’s motivation. Guided successful short-term interventions were either not assessed with a long-term follow up ( 46 ) or they had little long-term effect on physical activity ( 26 ). Thus, we sought to identify factors that might motivate the patients to improve their lifestyle over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Since other studies reported a decrease in physical activity and fitness and an increase in weight gain during anticancer therapy ( 1 , 2 ), routine counselling appears to be insufficient to achieve a long-lasting effect on the patient’s motivation. Guided successful short-term interventions were either not assessed with a long-term follow up ( 46 ) or they had little long-term effect on physical activity ( 26 ). Thus, we sought to identify factors that might motivate the patients to improve their lifestyle over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly population, the adoption of a healthy lifestyle that includes PA has gained considerable attention due to its potential for cancer prevention as well as improving survival rates and boosting the QOL of cancer survivors [22]. Extensive research has consistently demonstrated [23][24][25] that escalating PA levels can signi cantly reduce cancer recurrence and mortality rates.…”
Section: Fact-l Comparison Of Patients With Different Demographic Cha...mentioning
confidence: 99%